New times, new trends for ethionamide: In vitro evaluation of drug-loaded thermally carbonized porous silicon microparticles - Nuno Vale (2012)
Multidrug-resistant tuberculosis (MDR-TB) has become a worldwide problem and a major public health concern. The mechanisms of resistance are fairly well characterized for most agents, but MDR limits the therapeutic usefulness of both new and classical medicines against TB. Ethionamide (ETA) is a thioamide antibiotic and one of the most widely used drugs as second line agent for the treatment of MDR-TB. Over the years, some studies have emerged to improve the bioavailability of this drug and of its active metabolites. However, inactive metabolites of ETA are still a major drawback in its application against TB. Porous silicon (PSi) materials can be applied to improve the dissolution behavior of poorly water-soluble compounds and to overcome toxicity and other drug-related problems in oral delivery. In the present work, we have loaded ETA into thermally carbonized-PSi (TCPSi) microparticles and studied the solubility, toxicity, permeability, and metabolic profiles of the PSi-loaded drug. The solubility and permeability of ETA was clearly enhanced after loaded into TCPSi particles at different pH-values. ETA was in general toxic at concentrations above 0.50 mM to HepG2. Caco-2, and RAW macrophage cells, but the toxicity was drastically reduced when the drug was loaded into the microparticles. ETA showed a fast metabolization process in the presence of the TCPSi particles. In addition, new thiolated metabolites were identified from incubation of ETA-loaded PSi with HepG2 liver cells, which opens new perspectives toward both the understanding of ETA metabolism and the development of novel ETA-based systems with improved efficacy against MDR-TB.